Effect of the type of coverage and some types of organic and chemical fertilizers in the growth and yield of potato plant Solanum tuberosum L. - Khazal, Zainah Hazbar (Journal of agricultural, environmental and veterinary sciences, 2019)
The experiment was conducted in one of the private fields in Diyala governorate. Cultivation was carried out in Autumn on September 15, 2013, and the harvest of tubers was on 25 December 2013. Reverie Elite class was used. A factorial experiment was carried out in Randomized Complete Block Design using two factors in three replicates. The differences between the averages were tested according to the L.S.D test at the level of probability 0.05. The first factor was mulching M included two treatments M1: mulching by wheat straw and M2: mulching by black plastic, the second factor F fertilization included four levels; F0 control without addition, F1 Chemical fertilizers as recommended (200, 240 and 600 kg/ ha for K2SO4, P2O5 and urea respectively), F2: fertilized by sheep compost at 5% and F3 spraying of amino acid proline with a concentration of 200 ppm.The results of the study showed that the treatment of black plastic (M2) is superior in the percentage of field maturity (100.00%), the number of plant stems (4.26), plant height (62.84 cm), the weight of the tuber (143.60 g) and plant yield (961.75), but The total number of tubers was not significantly different from wheat straw mulching. While fertilization treatments, proline (F3)was significantly increased number of stems (4.87), plant height (65.16) cm, tubers weight (159.80), plant yield (1158.16) g and the total yield (46.33) t ha-1. The germination rate did not differ significantly between the treatments.The interaction between fertilization with sheep compost and black plastic mulching with proline (M2F3) showed significant increasing in plant height (70.77) cm, number of tubers (7.60) weight of tuber (164.58) g, plant yield (1251.81 g) and total yield (m) 50.07 tons ha-1 except for germination ratio
Keywords: potatoes; field germination rate; proline; autumn sprouts